CALIBRATION METHOD AND ABSOLUTE MEASUREMENTS OF AIR KERMA OF DIAGNOSTIC X-RAY REFERENCE QUALITIES USING A FREE-AIR IONISATION CHAMBER. Issue 1 (28th October 2021) - Zhao, Rui; Wu, Jinjie; Wen, Yuqin; Lv, Yazhu; Guo, Bin; Liao, Zhenyu
Abstract: Accurate dose measurement is very important for diagnosing X-ray equipment. These equipment should be traced directly or indirectly to primary standard with as little uncertainty as possible. A parallel-plate free-air chamber was designed to measure air kerma of diagnostic X-ray absolutely. Different thickness of aluminium filters were used to obtain different radiation qualities according with IEC 61267. Correction factors were obtained by experiments and simulation, especially the air attenuation factor measured with vacuum method. The relative standard uncertainty of air kerma rate measurement was 0.46% and calibration factor was 0.53%. A transfer ionisation chamber was calibrated with Radiation Qualities in Radiation beams (RQR) qualities in National Research Council of Canada and National Institute of Metrology (NIM), the differences of calibration factors are less than 0.68%.